FORMATION AND DEVELOPMENT OF SCIENTIFIC AND INNOVATIVE INFRASTRUCTURE OF CLUSTERS IN UZBEKISTAN - Rajabov Juratbek; Kholikova Rukhsora Sanzharovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article highlights issues on the formation of scientific-innovative infrastructure of clusters of Uzbekistan. At the same time, the author has developed proposals for the formation of a scientific-innovative infrastructure that will promote the development of integration between cluster members, increase production efficiency, commercialization of innovative projects, develop and implement programs for the development of cotton-textile clusters.